Optically stimulated luminescence at room temperature of hydrothermal K 2 YF 5 :Pr 3+ crystals - Marcazzó, J. (2009)
In this paper optically stimulated luminescence (OSL)properties of Pr3+-doped double potassium yttrium fluoride(K2YF5) under green light stimulation at room temperature asa function of the doping concentration are reported. Besides,some characteristics concerning the possible application of thiscomposition as a new OSL dosimeter are presented, namely,the dose–response and fading of the OSL signal. The residualthermoluminescence (TL) response of K2YF5:Pr3+ after theOSL experiment has been investigated in order to establishwhether the traps responsible for OSL are also involved in theTL process. Spectral analysis of the OSL emission has beencarried out to determine the role played by Pr3+ ions in theradiative relaxation process. Finally, the total OSL output ofK2YF5:Pr3+ is compared to that of commercial Al2O3:C.